Profitability of Contrarian Strategies: Evidence From the Stock Exchange of Mauritius - Subadar, Ushad Agathee; Hossenbaccus A. R., Muhammad Anas (Organizations and Markets in Emerging Economies, 2018)
The aim of this paper is to assess the profitability of contrarian strategies on the Stock exchange of Mauritius. Using data from 2001 till 2009 for all 40 listed companies on the official market, the study shows little support in favour of the contrarian effect. In particular, the losers portfolio seems to outperform the winners portfolio in one out of nine strategies. However, when considering the market return, negative excess returns are noted for all portfolios across all strategies, providing strong support for a passive portfolio management strategy and weak support for overreaction hypothesis. In addition, the Size, Price, Earnings to Price (E/P) and Book to Market (B/M) Effect has been tested. The results suggest that the average market return is greater than size-based portfolios and price-based portfolios. However, when accounting for the E/P and the B/M effect, there seems to be a strategy which can beat the market. Nevertheless, most strategies for E/P and B/M portfolios indicate insignificant excess returns. In general, the results of this paper are undoubtedly in sharp contrast with most popular studies in developed markets. However, it is observed that investors on the SEM may not possess similar characteristics to those of well-advanced markets. In particular, according to Harvey (1995), emerging market countries are sometimes relatively isolated from capital markets of other countries.